2021
DOI: 10.1002/smr.2403
|View full text |Cite
|
Sign up to set email alerts
|

MARS: Detecting brain class/method code smell based on metric–attention mechanism and residual network

Abstract: Code smell is the structural design defect that makes programs difficult to understand, maintain, and evolve. Existing works of code smell detection mainly focus on prevalent code smells, such as feature envy, god class, and long method. Few works have been done on detecting brain class/method. Furthermore, existing deep‐learning‐based approaches leverage the CNN model to improve accuracy by barely increasing the number of layers, which may cause a problem of gradient degradation. To this end, this paper propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Their results presented that the accuracy and validity of these two methods for detecting code smell still need further investigation. Some studies Sharma et al (2021); Yu et al (2021); Zhang and Dong (2021); Li and Zhang;Zhang et al (2022) tried to apply deep learning techniques for CSD, and their conclusions examined that some deep learning models accept a better performance on CSD, i.e., Convolutional Neural Networks (CNN-1) Sharma et al (2021); Zhang et al (2022), recurrent neural network Sharma et al (2021), long short-term memory Yu et al (2021); Li and Zhang, residual network Zhang and Dong (2021), and attention Zhang et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results presented that the accuracy and validity of these two methods for detecting code smell still need further investigation. Some studies Sharma et al (2021); Yu et al (2021); Zhang and Dong (2021); Li and Zhang;Zhang et al (2022) tried to apply deep learning techniques for CSD, and their conclusions examined that some deep learning models accept a better performance on CSD, i.e., Convolutional Neural Networks (CNN-1) Sharma et al (2021); Zhang et al (2022), recurrent neural network Sharma et al (2021), long short-term memory Yu et al (2021); Li and Zhang, residual network Zhang and Dong (2021), and attention Zhang et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results presented that the accuracy and validity of these two methods for detecting code smell still need further investigation. Some studies [44][45][46][47][48] tried to apply deep learning techniques for CSD, and their conclusions examined that some deep learning models accept a better performance on CSD, that is, convolutional neural networks (CNN-1), 44,48 recurrent neural network, 44 long short-term memory, 45,47 residual network, 46 and attention. 48…”
Section: Machine Learning-based Csdmentioning
confidence: 99%
“…Zhang et al 28 introduced MARS, a brain-inspired method for code smell detection that relies on the Metric-Attention method. They applied various ML and Deep learning models and found that MARS outperformed conventional techniques in terms of accuracy.…”
Section: Background/literature Reviewmentioning
confidence: 99%